2017
DOI: 10.1016/j.celrep.2017.02.068
|View full text |Cite
|
Sign up to set email alerts
|

Human RAD52 Captures and Holds DNA Strands, Increases DNA Flexibility, and Prevents Melting of Duplex DNA: Implications for DNA Recombination

Abstract: SummaryHuman RAD52 promotes annealing of complementary single-stranded DNA (ssDNA). In-depth knowledge of RAD52-DNA interaction is required to understand how its activity is integrated in DNA repair processes. Here, we visualize individual fluorescent RAD52 complexes interacting with single DNA molecules. The interaction with ssDNA is rapid, static, and tight, where ssDNA appears to wrap around RAD52 complexes that promote intra-molecular bridging. With double-stranded DNA (dsDNA), interaction is slower, weake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 50 publications
4
29
0
Order By: Relevance
“…This compaction can be reversed by displacement of RAD52 from the ssDNA by the addition of either 7 M urea (not shown). These observations are consistent with the ring-like structure of RAD52 and the fact that its ssDNA-binding domain follows the circular contour of this surface, which would necessitate a reduction in the apparent end-to-end distance for any bound ssDNA, as has been previously reported (51). We find some striking similarities, as well as some notable differences, between the results we report here for human RAD52 and results we have previously reported for S. cerevisiae Rad52 (65).…”
Section: Rad52 Interactions With Recombination Intermediatessupporting
confidence: 90%
See 1 more Smart Citation
“…This compaction can be reversed by displacement of RAD52 from the ssDNA by the addition of either 7 M urea (not shown). These observations are consistent with the ring-like structure of RAD52 and the fact that its ssDNA-binding domain follows the circular contour of this surface, which would necessitate a reduction in the apparent end-to-end distance for any bound ssDNA, as has been previously reported (51). We find some striking similarities, as well as some notable differences, between the results we report here for human RAD52 and results we have previously reported for S. cerevisiae Rad52 (65).…”
Section: Rad52 Interactions With Recombination Intermediatessupporting
confidence: 90%
“…Rad52 is highly conserved, and human RAD52 shares many biochemical traits with its yeast counterpart (42,43). Like yeast Rad52, human RAD52 also forms ring-like structures (44 -47), binds tightly to ssDNA, and promotes ssDNA annealing (47)(48)(49)(50)(51). However, human RAD52 does not have a known mediator activity (42,43), and in striking contrast to S. cerevisiae, RAD52 deletions do not produce a strong phenotype in vertebrates (42,43,52,53).…”
mentioning
confidence: 99%
“…During RAD51--dependent GC process, RAD52 can also act on the annealing step, allowing the capture of the displaced strand by the resected second double--strand ends (Miyazaki et al, 2004;McIlwraith & West, 2008;Sugiyama et al, 2006;Brouwer et al, 2017). We show here that RAD51 blocks annealing when it is loaded on both complementary ssDNAs, which is the situation in both SSA and A--EJ.…”
Section: Discussionmentioning
confidence: 73%
“…Recently, it was reported that the DNA damage pathwaydependent regulation of Cep3 stimulates the SAC (54) and human Rad52 prevents force-induced DNA strand melting (55). In addition, some studies verified the involvement of components of the DNA damage pathway in the regulation of mitosis (35,56).…”
Section: Discussionmentioning
confidence: 97%